De facto international prosecutors in a global era : with my own eyes - Rankin, Melinda (Cambridge : Cambridge University Press, 2022)
In the past decades, great strides have been made to ensure that crimes against humanity and state-sponsored organized violence are not committed with impunity. Alongside states, large international organizations such as the United Nations and forums such as the International Criminal Court, 'de facto international prosecutors' have emerged to address these crimes. Acting as investigators and evidence-gathers to identify individuals and officials engaged in serious human rights violations, these 'private' non-state actors, and state legal 'officials' in a foreign court, pursue criminal accountability for those most responsible for core international crimes. They do so when local options to investigate fail and an international criminal tribunal remains unavailable. This study outlines three case studies of witnesses and victims who pursue those most responsible, including former heads of state. It examines their practices and strategies, and shows how witnesses and victims of core crimes emerge as key leaders in the accountability process.
Title from publisher's bibliographic system (viewed on 08 Aug 2022).
Keywords: Criminal procedure (International law); Crimes against humanity